Pengaruh Bauran Promosi terhadap Proses Keputusan Pembelian Gofood di Kota Bandung - Imanuddin Hasbi; Maya Alda Lestari (Jurnal Bisnis dan Akuntansi, 2022)
Currently the GoFood food delivery service application is very helpful for consumers, so this food delivery service is a solution in fulfilling these needs. GoFood needs to carry out various promotional strategies to be superior to its competitors who are actively promoting. This study aims to determine the response and how much influence partially the promotion mix on the Gofood purchasing decision process. This istudy uses a quantitative method of descriptive research. And iuse ia Likert scale as a measurement. The sampling technique uses incidental non-probability sampling technique. The population in this study are people who live in Bandung and have used Gofood services, from this population there are 100 samples to be studied. The data analysis technique used in this study is multiple linear regression analysis. The results showed that the promotion mix was in a good category, and the purchase decision process was in a good category. The promotion mix has a significant effect on purchasing decisions. The coefficient of determination test results obtained a value of 61%, while the remaining 39% was influenced by other factors not examined in this study. Based on the results of this study, GoFood should improve and maintain all dimensions of the promotional mix, where each dimension has a significant influence on purchasing decisions.